Penerapan Manajemen Kualitas Pelayanan untuk Meningkatkan Kepuasan Pelanggan - Lahagu, Artatina; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the influence of service quality and service quality management on customer satisfaction in restaurants. The theoretical basis used includes the Servqual model as a framework for measuring service quality and cognitive dissonance theory to understand customer satisfaction. Service quality is measured through the dimensions of service speed, staff friendliness, cleanliness of the place, and comfort of the atmosphere. In contrast, service quality management refers to the implementation of quality standards, service evaluation based on customer feedback, employee training, and quality control systems.Data were collected through a survey with a comprehensively designed questionnaire, involving 206 restaurant customers as samples. Data analysis employed multiple linear regression to assess the simultaneous influence of each variable on customer satisfaction. Â The results showed that service quality and service quality management both had a positive and significant influence on customer satisfaction. In particular, service speed and implementation of quality standards had the greatest influence in the regression model. This finding confirms that improving these aspects can effectively increase the level of customer satisfaction, which has an impact on customer loyalty and the potential for positive recommendations. Â Therefore, restaurants are advised to develop strategies to improve service quality and implement an effective quality management system to maintain competitiveness and business sustainability in the culinary industry.